Analytical Measurements and Efficient Process Generation Using a Dual–Arm Robot Equipped with Electronic Pipettes - Heidi Fleischer; Daniel Baumann; Shalaka Joshi; Xianghua Chu; Thomas Roddelkopf; Michael Klos; Kerstin Thurow (Energies, 2018)
The continued growth in life sciences is being accompanied by the constantly rising demand for robotic systems. Today, bioscreening and high–throughput screening processes are well automated. In contrast, a deficit can be found in the area of analytical measurements with complex and frequently changing processes. Robots undertake not only transportation tasks, but also direct sample manipulation and subsequent analytical measurements. Due to their human-like structure, dual-arm robots perform such processes similar to human operation. Liquid handling is required to transfer chemicals, to prepare standard solutions, or to dilute samples. Two electronic pipettes with different volume ranges (5–200 µL and 50–1000 µL) were integrated into a dual–arm robotic system. The main focus in this publication is the software interface for alternating robot and pipette control as well as the high–level process control system. The performance using a dual–arm robot equipped with electronic pipettes and conventional manual pipettes was determined and compared. The automation system presented is the first integration of a dual-arm robot in analytical measurement processes. Conventional manual laboratory pipettes and electronic pipettes are simultaneously used for liquid-handling tasks. The software control system enables a flexible and user-friendly process generation.